ANALISIS SEMIOTIKA PESAN MORAL PADA FILM “12 SUICIDAL TEENS” KARYA YUKIHIKO TSUTSUMI - Arawinda Nur Salsabyla; K. Y.S. Putri (Jurusan Ilmu Komunkasi FISIP Universitas Jenderal Soedirman, 2022)
Mass communication is the process of designing messages to be delivered to large audiences and spread over a wide geographic area, generally verbal or visual through media channels. Movie is a form of mass communication media. This research aims to describe the meaning of the moral message contained in